Lactacystin-induced kidney fibrosis: Protection by melatonin and captopril - Repova, Kristina; Stanko, Peter; Baka, Tomas; Krajcirovicova, Kristina; Aziriova, Silvia; Hrenak, Jaroslav; Barta, Andrej; Zorad, Stefan; Reiter, Russel J.; Adamcova, Michaela; Simko, Fedor (Frontiers in Pharmacology, 2022)
Lactacystin is a specific proteasome inhibitor that blocks the hydrolysis of intracellular proteins by ubiquitin/proteasome system inhibition. The administration of lactacystin to rats induced hypertension and remodeling of the left ventricle and aorta. This study tested whether lactacystin induces structural and fibrotic rebuilding of the kidneys and whether melatonin and captopril can prevent these potential changes. Six weeks of lactacystin administration to rats increased their average systolic blood pressure (SBP). In the kidneys, lactacystin reduced glomerular density, increased the glomerular tuft area, and enhanced hydroxyproline concentrations. It also elevated the intraglomerular proportion including the amounts of collagen (Col) I and Col III. Lactacystin also raised the tubulointerstitial amounts of Col I and the sum of Col I and Col III with no effect on vascular/perivascular collagen. Six weeks of captopril treatment reduced SBP, while melatonin had no effect. Both melatonin and captopril increased glomerular density, reduced the glomerular tuft area, and lowered the hydroxyproline concentration in the kidneys. Both drugs reduced the proportion and total amounts of intraglomerular and tubulointerstitial Col I and Col III. We conclude that chronic lactacystin treatment stimulated structural and fibrotic remodeling of the kidneys, and melatonin and captopril partly prevented these alterations. Considering the effect of lactacystin on both the heart and kidneys, chronic treatment with this drug may be a prospective model of cardiorenal damage suitable for testing pharmacological drugs as protective agents.